2021
DOI: 10.7759/cureus.17220
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency 10 kHz Spinal Cord Stimulation as a First Line Programming Option for Patients With Chronic Pain: A Retrospective Study and Review of the Current Evidence

Abstract: IntroductionNeuromodulation is an evolving and increasingly popular therapy for chronic pain management. Recent data suggest that novel waveforms have demonstrated greater benefit over traditional spinal cord stimulation (SCS). The authors conducted a retrospective review of patients undergoing high-frequency 10 kHz SCS at a single tertiary medical center for the purpose of contributing further evidence to this growing body of data. The literature of high-frequency SCS published to date was also reviewed. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Notably, our work represents the first study exploring the effect of 10 kHz stimulation as rescue therapy in patients previously treated with multiple waveforms with an inadequate pain relief: In fact, other studies investigated the possibility to use high‐frequency algorithms only to rescue ineffective traditional stimulation with an extremely variable response ranging from 46% to 81% 36 . The possible explanation of 10 kHz paradigm success in patients experiencing LoE of other waveforms can stand in the distinctive features of the high‐frequency stimulation which shares with DTM the capacity to restore the equilibrium between pro‐ and anti‐inflammatory cytokines and positively influence the activity of glial cells in addition to the above‐mentioned mechanism of action relating to the activation of inhibiting interneurons and medial pathway; furthermore, 10 kHz paradigm has been hypothesized to block depolarization signals, desynchronize neuronal signals, disrupt membrane integration, and inhibit spinal mitogen‐activated protein kinases 37,38 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, our work represents the first study exploring the effect of 10 kHz stimulation as rescue therapy in patients previously treated with multiple waveforms with an inadequate pain relief: In fact, other studies investigated the possibility to use high‐frequency algorithms only to rescue ineffective traditional stimulation with an extremely variable response ranging from 46% to 81% 36 . The possible explanation of 10 kHz paradigm success in patients experiencing LoE of other waveforms can stand in the distinctive features of the high‐frequency stimulation which shares with DTM the capacity to restore the equilibrium between pro‐ and anti‐inflammatory cytokines and positively influence the activity of glial cells in addition to the above‐mentioned mechanism of action relating to the activation of inhibiting interneurons and medial pathway; furthermore, 10 kHz paradigm has been hypothesized to block depolarization signals, desynchronize neuronal signals, disrupt membrane integration, and inhibit spinal mitogen‐activated protein kinases 37,38 …”
Section: Discussionmentioning
confidence: 95%
“…36 The possible explanation of 10 kHz paradigm success in patients experiencing LoE of other waveforms can stand in the distinctive features of the high-frequency stimulation which shares with DTM the capacity to restore the equilibrium between pro-and anti-inflammatory cytokines and positively influence the activity of glial cells in addition to the above-mentioned mechanism of action relating to the activation of inhibiting interneurons and medial pathway; furthermore, 10 kHz paradigm has been hypothesized to block depolarization signals, desynchronize neuronal signals, disrupt membrane integration, and inhibit spinal mitogen-activated protein kinases. 37,38 The switch to a different stimulation paradigm is one of the proposed strategies to overcome habituation, but other strategies have been also suggested. D'Souza et al reported a significant improvement of pain relief after a temporary interruption of stimulation, a phenomenon called holiday rescue analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, new techniques in neuromodulation are applied successfully for the treatment of PSPS2 with predominant back pain. [6][7][8][9] Especially higher frequency spinal cord stimulation (SCS) was reported to be effective for both leg and back pain compared with conventional SCS paradigms. 7 10 More than 60% of patients experienced an ODI improvement of ≥10 points after 1 year.…”
Section: Open Accessmentioning
confidence: 99%
“…According to Xu and colleagues, for patients with refractory PDN in the lower extremities, “SCS should be considered to reduce pain and improve quality of life.” 84 D’Souza and colleagues stated that SCS should be offered to patients who have refractory PDN and fail to benefit from conservative options, such as optimization of glucose control and neuropathic analgesic medications, before strong opioids are prescribed. 2 Meanwhile, current evidence favors a shift away from traditional SCS and toward paresthesia-free HF SCS 99 as first-line neuromodulation treatment 72,100 based on an accumulation of evidence showing better outcomes for HF SCS compared with traditional SCS 101-103 for many types of pain, including PDN.…”
Section: Current Recommendations For Using Scs For Pdnmentioning
confidence: 99%